Cultural intelligence in pharmacy education: A complex mixed methods study - Alosaimi, Norah (2022)
In providing health services, it is important not just to follow good care pathways but also to recognise the diversity in the population and adapt the way we care for patients to reflect this. If health professionals do not recognise the cultural needs of patients this is likely to result in poorer health outcomes for those patients. Whilst education is seen as the method of enhancing intercultural competence of future pharmacists, the diversity of the academic environment in which students learn can affect their development of intercultural competence. Ensuring students appreciate the impact of interculturally competent practice and providing them with the knowledge, skills and attitudes needed to be interculturally competent health professionals can result in better patient care. The literature suggests that pharmacists in the United Kingdom (UK) are not always competent in providing services to a diverse patient population. Few studies in the literature have considered the role of cultural education in pharmacy schools in the UK. This thesis aims to understand the cultural intelligence of pharmacy students and test an educational intervention at the University of Nottingham (UoN). The thesis employed a mixed methods approach through conducting a series of studies. Firstly, a questionnaire was distributed to all final year pharmacy students at the UoN (UK campus). Ninety-eight out of 241 (40%) students completed the questionnaire for the academic year 2017/18. Results suggest a lack of cultural knowledge and the need for cultural training. This was followed by semi-structured interviews with 35 final year pharmacy students, which found that students from different cultures had different attitudes towards their peers and raised student-chosen racial segregation as a barrier to effective intercultural contact. Finally, a novel educational intervention was designed and tested with 14 final year pharmacy students for the academic year 2018/19. The intervention focused on two areas, interaction with peers, and with patients. Results provide convincing evidence that suggest the need for wider testing of the effectiveness and duration of effect of the educational intervention. Despite the opportunities provided during their time at the UoN, students identified some challenges for educational providers in that their intercultural interactions and capability were affected by prior experiences, speaking more than one language, and sharing accommodation with people from different cultural backgrounds. This research was only implemented with one cohort of students in the School of Pharmacy at the University of Nottingham and so needs to be tested in other schools and institutions to provide a knowledge base that can direct future research and policies. Work also needs to be done at the organisational level to develop policies and practices that lead to positive outcomes in the community. The findings provide educators, researchers, students, and pharmacists with insights about factors that may facilitate or hinder the development of cultural intelligence among pharmacy students. These insights can be used to improve the academic environment and also training for pharmacists providing pharmaceutical services.